Sound and syllable distribution in written kannada and their application to speech and hearing - Jayaram M (Journal of All India Institute of Speech and Hearing, 1970)
The purpose of the present study was to compute the distribution of sounds and syllables in written Kannada. Simple frequency counts ofdifferent sounds (letters) and syllables were made from an analysis of more than 1 lakh words. The written material selected were news papersand popular magazines. The analysis showed the occurrence of 896 different syllables in Kannada with varying frequency of occurrence. Thepotential application of these statistics to (1) Communication engineering and (2) in the assesment, diagnosis, research and rehabilitation of individualswith speech, hearing and language pathology has been enumerated in the last section of the paper.